MANIFESTATIONS OF CYCLIC FLUCTUATIONS IN THE ECONOMY - Р. В. Грінченко (Ринкова економіка: сучасна теорія і практика управління)
The subject of the research in this article displays cyclical fluctuations at the macro, meso and micro levels of the economy. The aim of the article speaks theoretical basis manifestations of cyclical fluctuations in these levels of the economy, taking into account the study of the world experience. The main task of the state on the macro level is reducing the negative effects from the cyclic fluctuations. At the meso level anticyclical regulation should deal with regional authorities with the help of industry representatives. At the micro level or at the level of individual businesses hardest to prevent the negative consequences that can result from cyclical fluctuations in the economy. The theoretical information can give possibility to develop and provide effective measures to reduce the negative effects of cyclical fluctuations on the macro, meso and micro levels of the economy. Results of the study can be used in a counter-cyclical regulation at the level of the state, regions and individual enterprises.